IS26 Veers Genomic Plasticity and Genetic Rearrangement toward Carbapenem Hyperresistance under Sublethal Antibiotics - Da-Wei Wei; Nai-Kei Wong; Yuqin Song; Gang Zhang; Chao Wang; Juan Li; Jie Feng (mBio, 2022)
ABSTRACT Multidrug-resistant Gram-negative carriers of Klebsiella pneumoniae carbapenemases (KPCs) often subvert antibiotic therapy due to inadequate sensitivity in laboratory detection. Although unstable gene amplification has been recognized to crucially contribute to underestimation or misestimation of antimicrobial resistance in clinical isolates, the precise mechanisms underlying carbapenem resistance driven by amplification of blaKPC-2 remain obscure. Here, we reported that IS26-mediated amplification of blaKPC-2 rapidly and robustly gave rise to carbapenem hyperresistant phenotypes in an Escherichia coli clinical strain following sublethal meropenem or tobramycin preexposure. Intriguingly, IS26 also underpinned amplification of a 47 kb multiple drug resistance (MDR) region encompassing nine antibiotic resistance genes and six IS26 insertion sequences. Tandem-repeat analysis and experimental validation demonstrated that blaKPC-2 amplification was indeed mediated by IS26, which was further experimentally shown to involve intricate genetic rearrangement. Such gene amplification arose dynamically under antibiotic stress and subsided upon antibiotic withdrawal. Instead of reducing the amplification of the IS26-flanked MDR region, drug combinations in vitro exacerbated it. Our study, thus, provides valuable insights into how dynamic gene amplification processes can precipitously transform resistance status and complicate diagnosis. IMPORTANCE Klebsiella pneumoniae carbapenemases (KPCs) are powerful β-lactamases that enable Gram-negative pathogens to destroy clinically important carbapenems in antibiotic therapies. In particular, KPC-2 is difficult to detect due to a lack of instrument sensitivity in regular laboratory screens, which leads to misdiagnosis and poor treatment outcomes. It remains unclear how blaKPC-2 rapidly induces exceedingly high-level resistance against carbapenems following the challenges of sublethal antibiotics. Here, we demonstrated that, under sublethal doses of antibiotics, insertion sequence IS26 mediated rapid amplification of multiple resistance determinants, including blaKPC-2 and a multiple drug resistance (MDR) region, which was accompanied by intricate genetic rearrangement.